2022
DOI: 10.1039/d2cp01904c
|View full text |Cite|
|
Sign up to set email alerts
|

Quantifying the ion coordination strength in polymer electrolytes

Abstract: Quantitative determination of the cation coordination strength to the ligands in polymer electrolytes and its correlation to the ion transport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 54 publications
0
29
0
Order By: Relevance
“…This calls into question the validity of the FT-IR measurements on the polycarbonate electrolyte and may hint toward more general quantification problems for this and possibly also related polymer systems using vibrational spectroscopy, as has previously been observed for nitrile solvents. 38 The low Li + to TFSI oxygen coordination number for POHM suggests that it actually has a better solvating ability for LiTFSI as compared to the polyester and polycarbonate, which can also be seen in snapshots from Figure 5b. The Li + transport is affected by both the local coordination environment and the coordination strength.…”
Section: ■ Results and Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…This calls into question the validity of the FT-IR measurements on the polycarbonate electrolyte and may hint toward more general quantification problems for this and possibly also related polymer systems using vibrational spectroscopy, as has previously been observed for nitrile solvents. 38 The low Li + to TFSI oxygen coordination number for POHM suggests that it actually has a better solvating ability for LiTFSI as compared to the polyester and polycarbonate, which can also be seen in snapshots from Figure 5b. The Li + transport is affected by both the local coordination environment and the coordination strength.…”
Section: ■ Results and Discussionmentioning
confidence: 84%
“…It can be observed that the Li + to carbonyl oxygen coordination number for PCL is in good agreement with the coordination number from FT-IR; however, a difference in coordination number for PTeMC can be observed. This calls into question the validity of the FT-IR measurements on the polycarbonate electrolyte and may hint toward more general quantification problems for this and possibly also related polymer systems using vibrational spectroscopy, as has previously been observed for nitrile solvents . The low Li + to TFSI oxygen coordination number for POHM suggests that it actually has a better solvating ability for LiTFSI as compared to the polyester and polycarbonate, which can also be seen in snapshots from Figure b.…”
Section: Resultsmentioning
confidence: 97%
“…Nonetheless, it has long been considered that glymebased solutions are not ideal electrolytes for batteries as they possess a low dielectric constant and would poorly dissociate the ions. Depending on the chain length, glyme molecules can actually act as multidentate ligands, 47 and the solvated ions are highly stabilised through a chelating effect facilitated by the relatively low mechanical stress associated with the glyme strain. Long-chain glyme-based molecules, e.g., triglyme and tetraglyme, can thus dissolve a significant amount of salts, which can be used as electrolytes for rechargeable batteries.…”
Section: Discussionmentioning
confidence: 99%
“…However, without more samples and data points, it is not possible to assuredly draw firm conclusions from these parameters, and for this reason, further discussion will not be dealt with in this paper. Furthermore, FTIR spectra of PCL-PTMC:LiTFSI with and without zwitterions were recorded (see Figure S2), showing a change in the interaction between the carbonate and ester groups with the Li + but no apparent change in the 700 cm –1 region, which can be used to probe changes in the ion coordination …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, FTIR spectra of PCL-PTMC:LiTFSI with and without zwitterions were recorded (see Figure S2), showing a change in the interaction between the carbonate and ester groups with the Li + but no apparent change in the 700 cm −1 region, which can be used to probe changes in the ion coordination. 41 Voltammetric Measurements. The electrochemical stability of an electrolyte is conventionally evaluated with voltammetric measurements.…”
Section: ■ Results and Discussionmentioning
confidence: 99%